BMC Biology - Bell, Graham; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Biology is an open access, peer-reviewed journal that considers articles on all areas of biology. As a selective journal, published articles represents advances that are of high interest to a broad readership, as well as significant new findings, tools, and commentary in specialized sub-fields. The journal$1 (Bs scope covers primary research papers in any aspect of fundamental or applied biological sciences, or that bring insights into biological phenomena from related fields. The journal publishes primary content in Research, Methodology, Software and Registered Reports articles. Commissioned frontmatter Reviews, Perspectives, Forums and Comments provide authoritative coverage of important topics for the community. Submissions are handled by our team of in-house professional editors and expert Editorial Board Members.s
Keywords: Life sciences; Life Sciences